Cholestasis sepsis at neonatology ward and neonatal Intensive Care Unit Cipto Mangunkusumo Hospital 2007 : incidence, mortality rate and associated risk factors (Medical Journal of Indonesia, 2008)
Cholestatic jaundice represents serious pathological condition. Septic-cholestasis is a kind of hepato-cellular cholestasis that occured during or after sepsis caused by biliary flow obstruction. This is a cohort study from February to June 2007 on neonatal sepsis patients at Neonatology ward Department of Child Health Faculty of Medicine University of Indonesia-Cipto Mangunkusumo General National Hospital. Aim of this study is to find out the incidence of intrahepatic cholestasis in neonatal sepsis, associated risk factors, and mortality rate in neonatal cholestasis-sepsis. From 138 neonatal sepsis patients, the incidence of intrahepatic cholestasis is 65.9%. None of the risk factors tested in this study showed statistically significant result. Mortality rate of neonatal cholestasis-sepsis is 52.8%. (Med J Indones 2008; 17: 107-13)